(untitled) (Journal of the College of Basic Education, 2024)
One of the goals of the science of theology is to establish evidence and remove suspicions. The rational and transmission evidence is linked to the Islamic faith, and with this close connection, it was necessary to shed light on the formation of evidence, its selection, advancement, development, and renewal among theologians. The study aimed to control the methodology of verbal reasoning and develop it, leading to the renewal of the science of theology in terms of reasoning. and methodology in the future